Assessment of the external validity of the AJCC 8 th staging system for small intestinal adenocarcinoma: a time to reconsider the role of tumor location? - Oweira, Hani; Mehrabi, Arianeb; Reißfelder, Christoph (Journal of gastrointestinal oncology, 2019)
Background: The current study evaluates the validity and performance of the 8 th edition of the American Joint Committee on Cancer (AJCC) staging system for small intestinal adenocarcinoma patients. - Methods: Surveillance, Epidemiology and End Results (SEER) database [2004-2015] was explored and AJCC 6th, 7 th , and 8 th versions were assigned for each patient. Through Kaplan-Meier estimates, overall survival analyses were conducted. Cox regression analysis (adjusted for age, race, gender, sub-site, grade and surgical treatment) was conducted for cancer-specific survival and additionally, pairwise hazard ratio comparisons were performed. - Results: A total of 2,997 small intestinal adenocarcinoma patients were eligible and included in the analysis. Overall survival was compared according to the three AJCC staging systems. For the three versions, the P value for the trend in overall survival was significant (P th and 8 th stages were also performed, and all comparisons were significant (P vs . IIIA. C-statistic (using death from small intestinal adenocarcinoma as the dependent variable) for AJCC 6th staging system was: 0.645 [standard error (SE): 0.011; 95% CI: 0.623-0.668]; for c-statistic for AJCC 7 th staging system was 0.658 (SE: 0.011; 95% CI: 0.637-0.680); while c-statistic for AJCC 8 th staging system was 0.660 (SE: 0.011; 95% CI: 0.638-0.682). Multivariate analysis of factors affecting cancer-specific survival suggested that older age (P=0.005), higher lymph node ratio (P Conclusions: There is no evidence that AJCC 8 th system provided better prognostic characterization compared to previous AJCC staging systems for small intestinal adenocarcinoma. Subsite-specific staging paradigms should be explored in future editions of the staging system.
Gesehen am 18.07.2019